Effect of solid-state fermentation using Aspergillus oryzae and Aspergillus niger on bitter and bioactive compounds of Moringa oleifera seed flour - Candytias Puspitasari; Praphan Pinsirodom; Songsak Wattanachaisaereekul (LWT, 2024)
Moringa seeds are a valuable source of phenolics and antioxidants when incorporated into food formulations. However, they also have a characteristic bitter taste attributed to the presence of glucosinolate compounds. This study aimed to assess the impact of solid-state fermentation (SSF) with monocultures and co-cultures of Aspergillus oryzae (AO) and Aspergillus niger (AN) on the levels of glucosinolate and phenolic compounds in moringa seed flour. After autoclave sterilization, the most significant reduction of glucosinolates was observed in samples fermented via AO:AN (1:1) co-culture, accompanied by a notable increase in myrosinase activity. Meanwhile, total phenolic and tannin content were most markedly increased with AO:AN (1:2) co-culture following autoclave sterilization. Assays measuring antioxidant activity (DPPH, ABTS, and FRAP) also showed substantial enhancement after fermentation. Pearson Correlation analysis indicated tannins to feature prominently in the antioxidant activity of moringa seed flour. All told, the results demonstrate SSF with AO:AN co-culture to be effective in reducing glucosinolates, elevating phenolic compounds, and enhancing antioxidants, the fermented flour also exhibited a noteworthy increase in protein content. These findings highlight the promising potential of fermented moringa seed flour in developing food products. • Solid-state fermentation with A. oryzae and A. niger produces myrosinase, which degrades glucosinolates. • Co-culture is more efficient than monoculture in diminishing the glucosinolate content of moringa seed flour. • A 1:2 co-culture of A. oryzae and A. niger boosts phenolics and antioxidants in moringa seed flour. • Fermentation enhances the protein content of moringa seed flour.
Keywords: Moringa oleifera research and applications; Proteins in Food Systems; Microencapsulation and Drying Processes